2015
DOI: 10.2220/biomedres.36.89
|View full text |Cite
|
Sign up to set email alerts
|

<b>Basic helix-loop-helix transcription factor DEC1 regulates the cisplatin-induced apoptotic pathway of human esophageal cancer </b><b>cells </b>

Abstract: DEC1[basic helix-loop-helix (BHLH) E40/Stra13/Sharp2] and DEC2 (BHLHE41/Sharp1) are BHLH transcription factors that are associated with the regulation of apoptosis, cell proliferation, and circadian rhythms, as well as malignancy in various cancers. However, the roles of DEC1 and DEC2 expression in esophageal cancer are poorly understood. In this study, we examined the roles of DEC1 and DEC2 in human esophageal cancer TE 5 and TE 10 cells that had been treated with cis-diamminedichloroplatinum (II) (cisplatin:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…E-box is ubiquitously expressed in the promoter of target genes, including E-cadherin, occludins, and claudins (Ikenouchi et al 2003 ). DEC1 directly regulate the target genes involved in many cancer cells (Bi et al 2015 ; Seino et al 2015 ). There are some similarities between carcinoma and IPF, so we examined whether DEC1 is involved in pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…E-box is ubiquitously expressed in the promoter of target genes, including E-cadherin, occludins, and claudins (Ikenouchi et al 2003 ). DEC1 directly regulate the target genes involved in many cancer cells (Bi et al 2015 ; Seino et al 2015 ). There are some similarities between carcinoma and IPF, so we examined whether DEC1 is involved in pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…This results in elevated HIF-1α expression to suppress ASS1 for synthetic lethality by ADI-PEG20. Previous studies have demonstrated that expression of DEC1 can be regulated by many environmental stimuli, including nutritional feeding [37], growth factor [38], and genotoxic agents [39, 40]. In mammalian cells, DEC1 functions as a repressor for the circadian transcriptional regulators CLOCK/BMAL through promoter E-box binding [20].…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that BHLHE40 overexpression is a protective mechanism against ESCC progression. A second study using esophageal cancer cell lines showed that BHLHE40 overexpression promoted www.Genes&Cancer.com apoptosis as indicated by an increase in PARP cleavage [86]. Thus, while IEN is characterized by an increase in BHLHE40, progression to ESCC is characterized by its decrease.…”
Section: Cancers Where Bhlhe40 Expression Is Bimodal: Esophageal Carcmentioning
confidence: 99%
“…In colon cancer, BHLHE40 overexpression impeded serum deprivationinduced apoptosis and selectively inhibited the activation of procaspases related to the intrinsic death pathway (precaspase 3, 7, 9), without affecting the extrinsic death pathway [79]. On the other hand, a study using esophageal cancer cell lines showed that BHLHE40 overexpression promoted apoptosis as indicated by an increase in PARP cleavage [86]. This contrast can be explained by investigation of the downstream targets of BHLHE40 in cancers where it either promotes or inhibits apoptosis.…”
Section: Dual Effect Of Bhlhe40 On Apoptosismentioning
confidence: 99%